Aberrant HSP90 Expression in Lymphocytes and HSP90 Response to Anti-PD-1 Therapy in Lymphoma Patients - Albakova, Zarema; Mangasarova, Yana; Albakov, Akhmet; Nikulina, Elena; Kravchenko, Sergey; Sapozhnikov, Alexander (Frontiers in Immunology, 2022)
HSP90 family of molecular chaperones has been shown to be implicated in various stages of tumor growth and development. Recent studies have highlighted the role of extracellular HSP90 in tumor immunology, however, the role that HSP90 plays in the regulation of immune responses and the impact of cancer immunotherapy, including immune checkpoint blockade, on HSP90 is still unclear. Here we assessed the surface and intracellular expression of constitutive cytosolic HSP90β isoform, mitochondrial HSP90 homolog TRAP1 and co-chaperone STIP1/HOP in T, NK, B and NKT cells derived from peripheral blood and bone marrow samples of patients with Hodgkin and B-cell Non-Hodgkin lymphomas. HSP90β and STIP1 were overexpressed in B lymphocytes, while TRAP1 expression was decreased in T, B, NK and NKT cells of lymphoma patients. HSP90 overexpression in B cells was not associated with malignant B cell clones, since no clonotypic B cells were detected by immunoglobulin heavy chain (IgH) gene rearrangements. PD-1 blockade was found to differently affect the intracellular and surface HSP90 in T, B, NK and NKT cells in patients with relapsed or refractory classical Hodgkin lymphoma. Modulating HSP90 was found to affect the NK cell degranulation response and IFNγ production in lymphoma patients. These findings provide the rationale to further explore HSP90 homologs for improving patient response to cancer immunotherapy